Gamified mathematics practice: Designing with e-commerce and computational concepts. - Lee, Chien Sing *; Wong, Jing Wen; Ee, Peh Yenc (2017)
learning Mathematics: first, students who face difficulty understanding and are too shy to participate in discussions and subsequently do not manage to resolve their doubts, and second, dull e-learning websites. The many rules in Mathematics compounds the problem further. We thus aim to address these problems through a gamified-commerce oriented Mathematics learning practice system, Alzebra, for informal learning. Focusing on principles of Information Systems Analysis and Design, e-commerceoriented computational concepts are embedded in the game to motivate online practice. The system concept, design methodology and user testing outcomes are presented. Significance lies in deriving perception towards gamification and components which users liked or disliked and the efficacy of our hybrid approach in systems development.